Avaliação do desempenho da cobrança da água bruta por categoria de uso nas Bacias do Estado do Ceará utilizando a análise por envoltória de dados - Rodrigues, Marcus Vinícius Sousa (2014)
The scarcity of water resources can cause serious conflicts of interest due to its multiple uses. The management of water resources in a watershed is the safest way to ensure these multiple uses, through the adoption of instruments, such as charging for water use. The collection has been implemented very slowly in Brazil, even though the trust of the Law No. 9433/97 and State Policies on Water Resources. The charge for the use of raw water in Ceará began in 1996 and the Water Resources Management Company of Ceará - COGERH, as the agency responsible for its calculation and its implementation. To date no work has been done in order to evaluate the performance of this instrument by use category in the watersheds of the State of Ceará. The main objective of this doctoral work is to propose a methodology through data envelopment analysis, to evaluate the performance of the instrument of charging for the use of raw water applied the main use categories (industrial, public supply and irrigation) in the basins river of Ceará. The proposed performance analysis model was composed of six variables (with four inputs and two outputs) and the method used was the DEA-BCC, with the output orientation, as computational tool using the DEA-Solver, professional version 7.0 software. Altogether 33 DMUs of all Ceará basins were analyzed. These units, thirteen were classified as efficient and consequently twenty were classified as inefficient. The set of 33 DMUs showed an average efficiency of approximately 64.80%. The sector that has proved more efficiently throughout the state was the industry with an average efficiency of about 97.97%, followed by public supply sector with an average efficiency of approximately 68.17%. The irrigation sector was the most inefficient industry throughout the state, with an average efficiency measure equal to approximately 28.25%. Altogether eight DMUs irrigation presented with very low efficiencies, measures below 6.5%, highlighting negatively to DMU24 (Acaraú basin), as the most inefficient unit all analyzed together with a relative efficiency of approximately 0.08%. Among the criteria used for analysis stand out iuo index (granted users) and IBH index (water balance) inputs, and outputs IFVC (billing index volume consumed) and TMF (average billing rate). In relation to the criteria proposed in this paper, we can observe water users which are in disagreement with the laws in force in the State in relation to water resources, billed as users who do not have licenses or users who have higher intakes their grants.